2018
DOI: 10.21037/tcr.2018.07.09
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of molecular hydrogen in ovarian cancer

Abstract: Background: To investigate the potential effects of molecular hydrogen on ovarian cancer.Methods: The in vivo study was performed using Hs38.T xenografted BALB/c nude mice. The mean tumor volume was monitored during 6 weeks of hydrogen inhalation. Immunohistochemistry (IHC) staining was performed to determine the Ki67 and CD34 expression. The in vitro effects of molecular hydrogen on proliferation of Hs38.T and PA-1 were determined by Cell Counting Kit (CCK)-8 assay. Matrigel invasion assay was performed to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…The results showed that hydrogen treatment suppressed migration, invasion, and the colony-forming ability in both C6 and U87 cells. We reported similar effects in a previous study on ovarian cancer cells [11]. A hallmark of GBM is the extensive invasion of tumor cells into the normal brain tissues and along the vascular tracks, which prevents complete resection of all malignant cells [3, 29].…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The results showed that hydrogen treatment suppressed migration, invasion, and the colony-forming ability in both C6 and U87 cells. We reported similar effects in a previous study on ovarian cancer cells [11]. A hallmark of GBM is the extensive invasion of tumor cells into the normal brain tissues and along the vascular tracks, which prevents complete resection of all malignant cells [3, 29].…”
Section: Discussionsupporting
confidence: 81%
“…The effects of molecular hydrogen on cancer have been reported in several types of tumors including skin squamous cell carcinomas [7], lung cancer [9, 10], ovarian cancer [11], thymic lymphoma [12], liver tumors [13, 17], renal cell carcinoma [14], and colon cancer [16, 18]. However, whether molecular hydrogen has an anti-tumor effect on GBM has remained unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the past 10 years, H 2 has been used to treat cancer and metabolic disease or to correct ischemia and reperfusion injury of various organs, taking advantage of its high bio-safety [20][21][22]. With respect to cancer, hydrogen can inhibit cellular activity, proliferation, invasion, and migration in a dose-and time-dependent manner; promote apoptosis in cervical cancer, breast cancer, cutaneous melanoma [23], ovarian cancer [24], lung cancer [25], colon cancer [26], thymic lymphoma [27], Ehrlich ascites tumor cells [28], oral squamous cell carcinoma, and fibrosarcoma cells [29]; reduce tumor volume and weight; and inhibit tumor growth in xenografted mice, thus prolonging the survival of tumor-bearing mice [23]. H 2 also reduces renal toxicity in patients undergoing radiotherapy and chemotherapy [30].…”
Section: Introductionmentioning
confidence: 99%